Effects of the Patellar Tendon Strap on Kinematics, Kinetic Data and Muscle Activity During Gait in Patients With Chronic Knee Osteoarthritis - Eun-Ji Lee; Ki-Song Kim; Young-In Hwang (Korean Research Society of Physical Therapy, 2023)
Background: Osteoarthritis is a common condition with an increasing prevalence and is a common cause of disability. Osteoarthritic pain decreases the quality of life, and simple gait training is used to alleviate it. Knee osteoarthritis limits joint motion in the sagittal and lateral directions. Although many recent studies have activated orthotic research to increase knee joint stabilization, no study has used patellar tendon straps to treat knee osteoarthritis. Objects: This study aimed to determine the effects of patellar tendon straps on kinematic, mechanical, and electromyographic activation in patients with knee osteoarthritis. Methods: Patients with knee osteoarthritis were selected. After creating the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), leg length difference, Q-angle, and thumb side flexion angle of the foot were measured. Kinematic, kinetic, and muscle activation data during walking before and after wearing the orthosis were viewed. Results: After wearing the patellar tendon straps, hip adduction from the terminal stance phase, knee flexion from the terminal swing phase, and ankle plantar flexion angle increased during the pre-swing and initial swing phases. The cadence of spatiotemporal parameters and velocity increased, and step time, stride time, and foot force duration decreased. Conclusion: Based on the results of this study, the increase in plantar flexion after strap wearing is inferred by an increase due to neurological mechanisms, and adduction at the hip joint is inferred by an increase in adduction due to increased velocity. The increase in cadence and velocity and the decrease in gait speed and foot pressure duration may be due to joint stabilization. It can be inferred that joint stabilization is increased by wearing knee straps. Thus, wearing a patellar tendon strap during gait in patients with knee osteoarthritis influences kinematic changes in the sagittal plane of the joint.